The protective effects of ligustrazine on ischemic stroke: a systematic review and meta-analysis of preclinical evidence and possible mechanisms - Wang, Ziming; Wu, Zihong; Miao, Yifan; Hao, Aohan; Chen, Hao; Zhao, Shuang; Luo, Min; Guo, Shihan; Liu, Yingming; Lu, Yun (Frontiers in Pharmacology, 2024)
Introduction: The objective of this study is to systematically evaluate the effect of ligustrazine on animal models of ischemic stroke and investigate its mechanism of action. Materials and Methods: The intervention of ligustrazine in ischemic diseases research on stroke model animals was searched in the Chinese National Knowledge Infrastructure (CNKI), Wanfang Database (Wanfang), VIP Database (VIP), Chinese Biomedical Literature Database (CBM), Cochrane Library, PubMed, Web of Science, and Embase databases. The quality of the included literature was evaluated using the Cochrane risk of bias tool. The evaluation included measures such as neurological deficit score (NDS), percentage of cerebral infarction volume, brain water content, inflammation-related factors, oxidative stress-related indicators, apoptosis indicators (caspase-3), and blood-brain barrier (BBB) permeability (Claudin-5). Results: A total of 32 studies were included in the analysis. The results indicated that ligustrazine significantly improved the neurological function scores of ischemic stroke animals compared to the control group (SMD = −1.84, 95% CI −2.14 to −1.55, P < 0.00001). It also reduced the percentage of cerebral infarction (SMD = −2.97, 95% CI −3.58 to −2.36, P < 0.00001) and brain water content (SMD = −2.37, 95% CI −3.63 to −1.12, P = 0.0002). In addition, ligustrazine can significantly improve various inflammatory factors such as TNF-α (SMD = −7.53, 95% CI −11.34 to −3.72, P = 0.0001), IL-1β (SMD = −2.65, 95% CI −3.87 to −1.44, P < 0.0001), and IL-6 (SMD = −5.55, 95% CI −9.32 to −1.78, P = 0.004). It also positively affects oxidative stress-related indicators including SOD (SMD = 4.60, 95% CI 2.10 to 7.10, P = 0.0003), NOS (SMD = −1.52, 95% CI −2.98 to −0.06, P = 0.04), MDA (SMD = −5.31, 95% CI −8.48 to −2.14, P = 0.001), and NO (SMD = −5.33, 95% CI −8.82 to −1.84, P = 0.003). Furthermore, it shows positive effects on the apoptosis indicator caspase-3 (SMD = −5.21, 95% CI −7.47 to −2.94, P < 0.00001) and the expression level of the sex-related protein Claudin-5, which influences BBB permeability (SMD = 7.38, 95% CI 3.95 to 10.82, P < 0.0001). Conclusion: Ligustrazine has been shown to have a protective effect in animal models of cerebral ischemic injury. Its mechanism of action is believed to be associated with the reduction of inflammation and oxidative stress, the inhibition of apoptosis, and the repair of BBB permeability. However, further high-quality animal experiments are required to validate these findings.